Comparison of a Novel Formulation of Abiraterone Acetate vs. the Originator Formulation in Healthy Male Subjects: Two Randomized, Open-Label, Crossover Studies - Goldwater, Ronald; Hussaini, Azra; Bosch, Bill; Nemeth, Paul (Clinical pharmacokinetics, 2017)
Background and Objective Abiraterone acetate is approved for the treatment of metastatic castration-resistant prostate cancer. The originator abiraterone acetate (OAA) formulation is poorly absorbed and exhibits large pharmacokinetic variability in abiraterone exposure. Abiraterone acetate fine particle (AAFP) is a proprietary formulation (using SoluMatrix Fine Particle Technology™) designed to increase the oral bioavailability of abiraterone acetate. Here, we report on two phase I studies in healthy male subjects aged 18–50 years. Methods In Study 101, 20 subjects were randomized in a crossover design to single doses of AAFP 100, 200, or 400 mg or OAA 1000 mg taken orally under fasting conditions. Results suggested that AAFP 500 mg would be bioequivalent to OAA 1000 mg in the fasted state. To confirm the bioequivalence hypothesis and to further expand the AAFP dose range, in Study 102, 36 subjects were randomized in a crossover design to single doses of AAFP 125, 500, or 625 mg or OAA 1000 mg. Both studies included a 7-day washout period between administrations. Results Dose-dependent increases in the area under the plasma concentration–time curve and maximum plasma concentration with AAFP were observed in both studies. The AAFP 500-mg bioavailability relative to OAA 1000 mg measured by the geometric mean ratio for area under the plasma concentration–time curve from time zero to the time of the last quantifiable concentration was 93.4% (90% confidence interval 85.3–102.4), area under the plasma concentration–time curve from time zero to infinity was 91.0% (90% confidence interval 83.3–99.4), and maximum plasma concentration was 99.8% (90% confidence interval 86.3–115.5). Dose proportionality was seen across all AAFP dose levels (100–625 mg). Abiraterone acetate fine particle was found to be safe and well tolerated in this study. Conclusion Abiraterone acetate fine particle 500 mg was demonstrated to be bioequivalent to OAA 1000 mg in healthy volunteers under fasted conditions.